Comment on “DNA damage is a pervasive cause of sequencing errors, directly confounding variant identification” - Stewart, Chip (Science, 2018)
Chen et al. (Reports, 17 February 2017, p. 752) highlight an important problem of sequencing artifacts caused by DNA damage at the time of sample processing. However, their manuscript contains several errors that led the authors to incorrect conclusions. Moreover, the same sequencing artifacts were previously described and mitigated in The Cancer Genome Atlas and other published sequencing projects.